(untitled) (Research, Society and Development, 2021)
Urinary incontinence (UI) is among the situations that reduce the quality of life of women, due to impairment in various areas of life, which leaves women vulnerable to various problems due to the restrictions that limit them. Urinary incontinence is not a specific pathology of elderly women, as the number of young women with this disorder has become relevant, affecting women at different stages of the life cycle. UI is among the situations that reduce the quality of life of women, due to impairment in various areas of life, such as physical, social and especially psychological, which leads to limitation of social and family activities. Due to lack of information, many women think that there is no treatment and imagine that this leakage of urine is normal. As a study methodology, we sought to gather articles that were important in the scientific field on the proposed topic. Despite the few studies found, we can conclude that urinary incontinence negatively affects the quality of life of women, especially with regard to the psychological sphere, making them unable to adequately perform their daily activities.